Ivotuk LAI Measurements. Version 1.0 ... - Copass, C.; Edwards, E.; Beringer, J. (UCAR/NCAR - Earth Observing Laboratory, 2007)
This dataset includes Leaf Area Index (LAI) measurements taken at peak biomass at the Ivotuk grid sites in 1998. For more information, see the readme file. ...